NILAI KARAKTER AKTIVITAS SOSIAL KEAGAMAAN KAMPUNG ARAB BANJARMASIN - Farhat Tifani (Universitas Lambung Mangkurat, 2018)
AbstractThe background of the writing is to lift, assemble and seek Arab Social Activities in the Arab village, as well as make it as a source of IPS Learning. The purpose of this writing is that we understand the life and social activities of diversity that see each other religiously as Arab villagers. The religious social activities of Arabs in Banjarmasin which are used as learning resources of social studies and can be performed by reviewing the religious social activities of Arab community that is religious, which is constektual for high school students / equal. In this paper used several things, systematic, factual and accurate to the facts, the nature and the relationship phenomenon. Interviews were conducted with Arab figures and people skilled in the art and qualified as informants. From the results of interviews in the data. Social Activity of creatures occurs directly through religious activities. The results show that the Arab village in Antasan Kecil Barat is a village that has a high religious value. This is a national character that can be used as a source of IPS lesson that is constektual for high school students/ equal.Keywords: Religious Social activity, Arab community, learning sources of social studies AbstrakLatar belakang penulisan adalah untuk mengangkat, merakit dan mencari Kegiatan Sosial Arab di desa Arab, serta menjadikannya sebagai sumber Pembelajaran IPS. Tujuan penulisan ini adalah agar kita memahami kehidupan dan aktivitas sosial keanekaragaman yang melihat satu sama lain secara agama sebagai warga desa Arab. Kegiatan sosial keagamaan orang-orang Arab di Banjarmasin yang digunakan sebagai sumber belajar ilmu sosial dan dapat dilakukan dengan meninjau kembali aktivitas sosial keagamaan komunitas Arab yang bersifat religius, yang merupakan konstektual bagi siswa SMA / sederajat. Dalam tulisan ini digunakan beberapa hal, sistematis, faktual dan akurat terhadap fakta, sifat dan fenomena hubungan. Wawancara dilakukan dengan tokoh-tokoh Arab dan orang-orang yang terampil dalam bidang ini dan memenuhi syarat sebagai informan. Dari hasil wawancara di data. Aktivitas sosial makhluk terjadi langsung melalui kegiatan keagamaan. Hasilnya menunjukkan bahwa desa Arab di Antasan Kecil Barat adalah desa yang memiliki nilai agama tinggi. Ini adalah karakter nasional yang dapat digunakan sebagai sumber pelajaran IPS yang konstektual bagi siswa SMA/sederajat.Kata Kunci: Kegiatan sosial keagamaan, komunitas arab, sumber belajar IPS